The prevalence of primary headache disorders in the adult population of Estonia. (June 2019) - Toom, Kati; Raidvee, Aire; Allas, Katri-Helena; Floria, Elina; Juhkami, Kristiina; Klimušev, Gustav; Leping, Maria; Liidemann, Margot; Milovidov, Alexander; Liivak, Karita; Paiste, Siiri; Paju, Gerli; et al.
Objective: To estimate the one-year prevalence of primary headaches, most importantly migraine and tension type headache, but also other primary headaches, in Estonia. Methods: A population-based random sample of 2162 subjects in Tartu City and Tartu County were interviewed by telephone or face to face using a previously validated questionnaire. Results: Of the 2162 contacted participants, 1215 (56%) fully completed the study. Of these, 502 (41.3%) reported headache during the previous year. The prevalences adjusted by weighting by age, gender, education, marital status and habitat were the following: All headaches 41.0%, all migraine 17.7%, all tension-type headache 18.0%, trigeminal autonomic cephalalgias 0.4%, other primary headaches 2.5%, and chronic headaches 2.7%. Conclusion: The 1-year prevalences of primary headache disorders in Estonia are comparable to the previous findings in other European countries.